Rapamycin Augments Human DC IL‐12p70 and IL‐27 Secretion to Promote Allogeneic Type1 Polarization Modulated by NK Cells. Issue 9 (22nd August 2013) - Macedo, C.; Turnquist, H. R.; Castillo‐Rama, M.; Zahorchak, A. F.; Shapiro, R.; Thomson, A. W.; Metes, D.
Abstract Mammalian target of rapamycin kinase inhibitor (mTORi) rapamycin (RAPA) use in transplantation can lead to inflammatory complications in some patients. Our goal was to better understand how mTORi‐exposed human monocyte‐derived dendritic cells (DC) stimulated with pro‐inflammatory cytokines shape T cell allo‐immunity. RAPA‐conditioned‐DC (RAPA‐DC) displayed a more immature phenotype than untreated, control (CTRL)‐DC. However, subsequent exposure of RAPA‐DC to an inflammatory cytokine cocktail (ICC) plus IFN‐γ induced a mature Type‐1 promoting phenotype, consisting of elevated HLA‐DR and co‐stimulatory molecules, augmented IL‐12p70 and IL‐27 production, but decreased IL‐10 secretion compared to CTRL‐DC. Co‐culture of mature (m)RAPA‐DC with allogeneic peripheral blood mononuclear cells resulted in significantly increased Type‐1 (IFN‐γ) responses by T cells. Moreover, NK cells acted as innate modulators that conveyed activating cell‐to‐cell contact signals in addition to helper (IFN‐γ) and/or regulatory (IL‐10) soluble cytokines. We conclude that production of IL12‐p70, IL‐27 and low IL‐10 by RAPA‐DC allowed us to elucidate how these cytokines as well as NK‐DC interaction shapes T cell allo‐immunity. Thus, lack of inhibitory NK cell function during allo‐specific T cell activation by human ICC + IFN‐γ‐stimulated RAPA‐DC may represent an unwanted effector mechanism that may underlie RAPA‐induced inflammatory events in transplant patients undergoing microbial infection or allograft rejection.